3D Evaluation of Porous Zeolite Absorbents Using FIB-SEM Tomography - Bae, Kiho; Kim, Jun Woo; Son, Ji-won; Lee, Tonghun; Kang, Sangkyun; Prinz, Fritz B.; Shim, Joon Hyung (KOREAN SOC PRECISION ENG, 2018)
An accurate characterization of the microstructure is of great importance in manufacturing zeolites for their appropriate use and optimal performance. Here, an analytical methodology suitable for the complex porous structures of zeolites using focused ion beam (FIB) and scanning electron microscopy (SEM) tomography is demonstrated. For this analysis, a commercial zeolite absorbent is chosen, which is composed of a single zeolite bead filled with small internal beads, like eggs in a brood pouch. Some of the internal zeolite beads and their surrounding pore structures have been precisely reconstructed as three-dimensional (3D) image forms over the micro-scale through FIB-SEM, and the microstructural properties such as particle/pore sizes, specific volume, and surface area are numerically evaluated from the image analysis. This study describes the details of the characterization process from sample preparation to image analysis and discusses major factors influencing the results.
Keywords: MICROSTRUCTURAL CHARACTERIZATION; ELECTRON-MICROSCOPY; FABRICATION; ADSORPTION; CARBON; RECONSTRUCTION; ANODE; 13X